The ALLELOPHATIC POTENTIAL OF WHEAT ROOT EXUDATES ON SEEDS GERMINATION AND SEEDLINGS GROWTH OF WILD MUSTARD (Sinapis arvensis L.) - ziaullah, syed muhammad; asim, Syed (Current Botany, 2019)
Wheat is very important cereal crop both for food and economy but this crop is severely effected by weeds diminish its quantity and quality. Sinapis arvensis L. (wild mustard) is common annual weed found in wheat field cause serious problems in the wheat fields and negatively affected its total yield. Allelochemicals have the potency to create weed management products which are ecofriendly. The experiment was designed with (three replications) of six wheat root exudates concentrations (0, 20, 40, 60, 80 and 100%), were tested on germination and seedling growth of wild mustard. The results showed as wheat root exudates concentration increased, its allelopathic effects on seeds germination and seedling growth rate of Sinapis arvensis also increased. Seed germination and seedling growth of Sinapis arvensis were reduced by increasing wheat root exudates concentration proves that its seeds were sensitive to it. Wheat root exudats at 100% concentration has more significant inhibitory effect on germination and seedling growth. The results demonstrated that usage of allelopathic behavior of wheat root exudates is an impressive method for biological control of wild mustard. Keywords: Wheat, Allelochemicals, Seed germination, Seedling growth, Wheat root exudates.